Software Development For On-Line Energy Monitoring And Control System Through The Web - Mohd Radzi, Mohd Amran (2002)
In Malaysia, the demand for energy continues to grow, while supplies remain constant (at best) and cost increases. The cost of increasing the energy supply in Malaysia is significant in such areas as construction of added electrical generation capacity, the cost of source energy materials, and the cost of transporting energy materials. By curbing the use of energy, the impact of increasing demand can be delayed. Furthermore, the reduction of energy use will counter the increasing cost per unit. There is a great potential for reducing the cost of electrical energy usage through introduction and application of Energy Management and Control System (EMCS). The EMCS consists of instrumentation control devices for data collection, monitoring and analyzing, and personal computers for automatic control system, which is primarily used to control the electrical demand of the user. The increasing use of internet application in information technology has given the option for this system to be developed for being connected to the internet. Internet and web based application are the current features available in this system.